2017
DOI: 10.1038/bmt.2016.318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wilms' tumor 1 expression on outcome of patients undergoing allogeneic stem cell transplantation for AML

Abstract: The monitoring of the minimal residual disease by Wilms' tumor 1 expression (MRD) is a standardized test, which can be used in over 80% of patients with AML. To investigate the prognostic value of MRD in patients undergoing allogeneic stem cell transplantation (allo-SCT) for AML, MRD was monitored 3 months after transplantation in 139 patients. MRD positivity did not lead to any therapeutic intervention. Median follow-up was 39.3 (6.4-99.8) months. Patients with positive MRD at 3 months experienced more often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Although the use of ASCT to consolidate patients with AML in CR1 has decreased over time, recent studies and guidelines have indicated that ASCT remains an interesting therapeutic option in good and intermediate risk patients, especially if minimal residual disease (MRD) is undetectable and/or molecular remission is documented . The combination of IV Busulfan and high dose Melphalan as conditioning regimen has been shown to be associated with a lower RI .…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of ASCT to consolidate patients with AML in CR1 has decreased over time, recent studies and guidelines have indicated that ASCT remains an interesting therapeutic option in good and intermediate risk patients, especially if minimal residual disease (MRD) is undetectable and/or molecular remission is documented . The combination of IV Busulfan and high dose Melphalan as conditioning regimen has been shown to be associated with a lower RI .…”
Section: Discussionmentioning
confidence: 99%
“…Although MFC-based AML MRD testing is applicable to most cases with a rapid turnaround, it also has a few limitations, including potential changes in phenotype over time, relatively less sensitivity, heterogeneity of leukemic phenotypes, operator-dependent bias because of the need for considerable expertise and experience, and subjective elements of analysis and data interpretation [2]. To identify another universal marker for MRD assessment, extensive efforts have been made to develop MRD tests targeting transcripts aberrantly expressed in AML [35,36], such as WT1 [17][18][19][20][22][23][24][25][26][27][28][29][30][31]. Overexpression of the WT1 gene in most patients with AML provides a target for novel immunotherapeutic approaches [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, ELN researchers used an optimized and standardized WT1 assay and established reference ranges for WT1 expression in normal blood and bone marrow (BM), with a large number of control samples, and transcript levels indicative of residual leukemia distinguished from background levels [22]. Despite several reports demonstrating the promising role of WT1 in MRD assessment under chemotherapy [22,23] and allo-HSCT settings [24][25][26][27][28][29][30][31], the WT1 MRD assay is not widely used in AML because of the lack of large-scale, controlled studies, particularly for allo-HSCT. Indeed, recent ELN guidelines for MRD in AML recommend the WT1 MRD assay only if other MRD assays, including flow cytometric ones, are unavailable as the condition to use a validated WT1 MRD assay by ELN researchers [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, circulating RNA in peripheral blood was also used as relapse prediction marker in HCT recipients [24]. Dulery et al [35] reported the value of WT1 quantitation in predicting relapse in the HCT setting; they used the same WT1 test (Ipsogen) in peripheral blood samples obtained in the post-HCT phase and identified the 3-month time point as the most useful. In a series of patients with AML treated with HCT, Rossi et al [36] observed that WT1 quantitation was most predictive at 3 months post-HCT, whereas MPFC was most useful before HCT and at day 30 post-HCT.…”
Section: Discussionmentioning
confidence: 99%